Analytical Approach to Model the Fade Depth and the Fade Margin in UWB Channels (2010)
In this paper, the variations of the ultrawideband (UWB) channel power as a function of the channel bandwidth are investigated. An analytical approach to characterize the fade depth and the fade margin due to small-scale fading in indoor environments is proposed. The approach is based on the IEEE 802.15.4a ultrawideband channel model and the assumption that the channel power can be modeled by a Gamma distribution. This analytical approach is checked by comparison with results derived through Monte Carlo simulations. The results show that the fade depth and the fade margin are closely related to the channel bandwidth. This analytical approach can be used to design and implement UWB communications systems. © 2006 IEEE.